Determining the crop planting calendar using T-test observation and Zoning Agro Climati and agricultural with Hotelling test in Kermanshah province - Behroz Sobhani; Vahid Safarian Zengir; Akhzar Karami (تحقیقات کاربردی علوم جغرافیایی)
The limitations and boundaries of agricultural production is dependent on climatic conditions. Weather is one of the most important factors in human activities, especially agriculture. Corn cultivation in the country's food supply is essential.  Kermanshah province, with the potential favorable climate, optimum conditions for corn are cultivated. The aim of this study was to investigate the role of precipitation and temperature in determining the agricultural calendar and to determine suitable areas for planting corn. To do this, climate data from 10 synoptic stations during the period of 20 years (1390-1371) were used. Use, Hoteling test and test observational data were analyzed. According to research, the station is under study, corn crop water demand in the months of June, July, August and September not secure and High temperature areas due to reduced need frequent in the months of May and June and in the lowlands due to a sharp increase in flowering time, seed maintenance and handling problems during the growing season makes this crop. Based on the results of Hotelling test 62 percent of the land area suitable Kermanshah province, 24 percent and 14 percent for maize is unsuitable. And also based on the results of t-test found 47 percent good, 38 percent moderate and 15 percent are unsuitable for corn. As a result, the central area of moderate temperatures for planting, eastern and northern areas of the southern and western areas of the province due to tropical cold and not suitable for maize cultivation.